أثر الاحتياطات الدولية والتصنيف الائتماني على الاستثمار الأجنبي المباشر في مصر - الغايش، مسعد محمد إسماعيل (جامعة بني سويف - كلية التجارة, 2017)
International reserves fell after the revolutions of January 2011 and July 2013 in Egypt. This was accompanied by a decrease in the sovereign credit rating of Egypt by the well-known international institutions that issued international credit ratings. This was also accompanied by a significant decrease in the ،low of FDI into the Egyptian economy, which invited the researcher to measure the impact of the previous two variables on the FDI. (Using Pearson correlation coefficient and multiple regression equation), the research found that there are three variables (growth rate + reserves + credit rating) contributed 75% of (FDI). Growth rate explained 48% of the total FDI)), followed by the reserves variable effect as interpreted by 13.6% , then credit rating at a rate of 13.1%. Find the need to maximize interest in the balance of international reserves because of their impact parameter of the determinants of FDI, as well as the role of credit rating, which is a testament to investors to ensure the economy's ability to fulfill Slate Commitments towards others. The need to increase exports and reduce dependence on the outside world enriched by the reduction of demand for the major currencies, particularly the dollar, to work to create an investment environment to attract more FDI, the need to promote the role of tourism and remittances from abroad and further upgrading of the Suez Canal services to increase the balance of Egypt hard currency.
انخفضت الاحتياطيات الدولية عقب ثورتي يناير 2011 ويوليو 2013 في مصر. وصاحب ذلك انخفاض في التصنيف الائتماني السيادي لمصر من قبل المؤسسات الدولية المعروفة التي تصدر التصنيفات الائتمانية الدولية. كما صاحب ذلك أيضا انخفاض ملحوظ في تدفق الاستثمارات الأجنبية إلى الاقتصاد المصري، ما دعي الباحث إلى قياس مدى تأثير المتغيرين السابقين على تدفق الاستثمارات الأجنبية إلى مصر (باستخدام معامل الارتباط لبيرسون، ومعادلة الانحدار المتعدد)، وقد خلص البحث إلى أن هناك ثلاث متغيرات (معدل النمو + الاحتياطيات + التصنيف الائتماني) أسهمت بنسبة 75% من صافي تدفقات (FDI) الداخلة إلى مصر، ويعد متغير معدل النمو الاقتصادي هو أكثر المتغيرات تأثيرا في تدفق الاستثمارات الأجنبية المباشر إلى مصر حيث فسر 48% من إجمالي (FDI)، تلاه في التأثير متغير الاحتياطيات حيث فسر 13.6%، ثم التصنيف الائتماني بمعدل 13.1% ولذا فإن تأثير متغيري الاحتياطي والتصنيف الائتماني ( 13.1 + 13.6 = 26.7%). وقد أوصى البحث بضرورة الاهتمام بتعظيم رصيد الاحتياطيات الدولية لما لها من تأثير كمحدد من محددات الاستثمار الأجنبي المباشر، فضلا عن دور التصنيف الائتماني الذي يعد بمثابة شهادة ضمان للمستثمرين لقدرة الاقتصاد على الوفاء بالالتزامات الدولة تجاه الآخرين. ضرورة زيادة الصادرات وخفض الاعتماد على العالم الخارجي بما يتضمنه من خفض الطلب على العملات الرئيسية وفي مقدمتها الدولار، العمل على تهيئة البيئة الاستثمارية لجذب المزيد من الاستثمارات الأجنبية المباشرة، ضرورة تشجيع دور السياحة وتحويلات العاملين من الخارج والمزيد من الارتقاء بخدمات قناة السويس لزيادة رصيد مصر من العملات الصعبة.
Keywords: مصر -- الاستثمار الأجنبي المباشر -- السياسة المالية -- الاحتياطات النقدية